Theoretical Rotordynamic Coefficients of Labyrinth Gas Seals: a Parametric Study on a Bulk Model - Paola Forte; Fabio Latini (International Journal of Rotating Machinery)
To date, available mathematical bulk models for the determination of linearized rotordynamic coefficients of labyrinth gas seals yield results which are not always in good agreement with the experimental ones. The object of this work is to discuss the limits of these models and to point out possible improvements and aspects that need further investigation.